The Eurozone’s Future: Nominal, Real and Structural Convergence - Rusek, Antonin (Archives of Business Research, 2016)
The future of the Eurozone will be determined by the convergence processes. The recent policy steps restored the nominal convergence as the sine qua non of the effectiveness of the common currency monetary policy. The same steps, however, deepened the real divergence. Structural convergence is then proposed as the answer to this conundrum. The term “structural” is then interpreted as the description of the set of preferences, political, economic, social and legal institutions and the associated policies and decisions. Structural convergence then describes the narrowing of the differencies between the national political, economic, social and legal institutions, which is expected to bring about the similar if not identical economic results as the response to the Europe wide economic policies. However, the subject is far from simple and it would be naïve to expect the quick results. History and traditions determine political, economic and structural characteristics of the Eurozone’s member countries. To overcome history is difficult, but not impossible.